PENGARUH PELATIHAN DAN DISIPLIN KERJA TERJADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada SPBE PT. Tunas Sejati Cilacap) - Kartikasari, Rizki Indah; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2017)
SPBE PT. Tunas Sejati Cilacap is one of the filling plant companies in Indonesia that performs the transportation, filling and delivery of LPG to the agents of PT. Pertamina which sells LPG. To be able to meet the needs of transportation, filling and delivery of LPG to agents in Cilacap and surrounding areas of course SPBE PT. Tunas Sejati Cilacap demands that employees can improve their performance. One way is to provide training so as to create quality human resources, in addition to the importance of work discipline also plays an important role in developing the potential of employees to optimize the company's activities to achieve goals.The purpose of this research is to analyze the effect of training and work discipline on employee performance with job satisfaction as intervening variabel. The data collected in this research using questionnaires distributed to respondents and samples used in this study is saturated samping technique with total samples of 67 respondents. The analysis used is multiple linear regression analysis method. The data testing technique used is validity test, reliability test, classical assumption test, coefficient determination test, F test, t test and sobel test to test the mediation effect.The results of analysis from this research result that training and work discipline have a positive and significant impact on job satisfaction, training and work discipline have a positive and significant impact to the employee performance, job satisfaction have a positive and significant impact on employee performance, job satisfaction mediates the effect of training on employee performance, and job satisfaction mediates the effect of work discipline on employee performance.